Pelatihan Pembuatan Google My Business Pada Pemilik Usaha Kedai Nyihah Penerima PMW (Program Mahasiswa Wirausaha) - Mahmud, Imam; Septianna, Erna Wahyu (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2024)
The development of information technology has changed the paradigm of obtaining information and communicating, making online presence essential for business success, especially for small and medium enterprises (SMEs). Google My Business (GMB) is a digital platform that increases the online visibility of business owners. Kedai Nyihah, a recipient of the Student Entrepreneurship Program (PMW), faced obstacles in utilizing digital technology due to limited knowledge and resources. This research uses intensive training methods to create and manage GMB profiles, strategies for responding to customer reviews, and utilization of additional features. The results of the training showed an increased understanding of Kedai Nyihah owners in managing GMB, including profile creation, image addition, and interaction with consumers. The training helped Kedai Nyihah increase its digital presence, attract more customers, and strengthen its position in the market. The GMB optimization training was effective in increasing Kedai Nyihah's visibility and sales, setting an important example for other SMEs regarding the adoption of digital technology to compete in the digital age.